Study of Variation in the Dialect of Various Region of India: Review - Patil, Shweta; Shivani U Patole, (International Journal of Scientific Research in Science and Technology, 2024)
‌Dialect refers to different characteristic of language of a specific group of speakers. These dialects are closely related and often mutually understandable, especially if close geographical region. Dialects can be sociolect, ethnolect, or regiolect, and can be associated with social class, ethnic group, or geographical/regional factors .Any variety of a language can classified as a dialect. Migration is most important factor for idiosyncrasy in languages in particular area. A region wise variation in language of people is know as dialect. Dialects is an important aspect of speaker variability. To express the individual  quality of specific  region. Children encounter multi-dialectal interactions. An review paper described techniques contributed for India regional language processing it gives information about sources of dataset for the Indian regional languages.
Keywords: Dialect,; Regional; Migration